A Proposed Model of Acceptance for Smart Glasses based Outdoor Augmented Reality Applications at UNESCO World Heritage Sites - Khalid Obeidy, Waqas; Arshad, Haslina; Yao Huang, Jiung (International Journal of Engineering and Technology, 2018)
With the advancements in the recent mobile and wearable technologies, opportunities in the digital tourism sector are on an all-time high. Although, there is only limited research on usersâ€™ acceptance of Augmented Reality (AR) in the cultural tourism context, previous researchers have explored the opportunities of using AR in order to enhance user acceptance and adoption. Recent AR research lack empirical studies and works that integrates dimensions which are specific to cultural heritage tourism and smart glass specific context. Hence, this work proposes an AR acceptance model in the context of cultural heritage tourism and smart glasses capable of performing augmented reality. Therefore, this work aims to discuss the methods needed to map the requirements and propose an AR acceptance model for Smart Glasses based wearable outdoor AR applications. The proposed model can be used to understand the AR usage behavior and visiting intention for tourists who use Smart Glass based AR at UNESCO cultural heritage sites in Malaysia. Furthermore, this work identifies technology readiness, visual appeal, information quality, and facilitating conditions as external variables and factors that may influence beliefs of visitors, their attitudes and intention of usage.Â Â